(3GdLhGfH GdCNdGbjI h GdegfjI aj JcfhdhLjG GdeYdheGJs - (3SYO YHO GdSJGQ egOj(B, (3GdegOGhjs ((3YeGf(B:s (3OGQ GdhQGb(B,s, 2009)
(3eONd Gdi GdGNdGbjGJ , Jbjje GdJcfhdhLjG h GdSjWQI YdjgG, eMaRGJ GdJZjjQ , Mbhb GdedcjI GdacQjI , GdNUhUjI , LQGFe GdMGShH , GdGNdGbjI GdegfjI , Gdegfjjf h GdGNdGbjGJ , GdYed aj bWGY JcfhdhLjG GdeYdheGJ , ejRGJ fXe GdeYdheGJ GdeMhSHI , HYV GdbhGfjf hGdeSGFd aj LQGFe GdMGShH , GdJWhjQ h GdJOQjH aj GdGNdGbjGJ (B.s
(3eQGLY U(B.231s
Keywords: (3BOGH GdegfIs; (3GdMhGSjHs; (3JcfhdhLjG GdeYdheGJs